Safety and efficacy of sargramostim (GM‐CSF) in the treatment of Alzheimer's disease. Issue 1 (24th March 2021) - Potter, Huntington; Woodcock, Jonathan H.; Boyd, Timothy D.; Coughlan, Christina M.; O'Shaughnessy, John R.; Borges, Manuel T.; Thaker, Ashesh A.; Raj, Balaibail A.; Adamszuk, Katarzyna; Scott, David; Adame, Vanesa; Anton, Paige; et al.
Abstract: Introduction: Inflammatory markers have long been observed in the brain, cerebrospinal fluid (CSF), and plasma of Alzheimer's disease (AD) patients, suggesting that inflammation contributes to AD and might be a therapeutic target. However, non‐steroidal anti‐inflammatory drug trials in AD and mild cognitive impairment (MCI) failed to show benefit. Our previous work seeking to understand why people with the inflammatory disease rheumatoid arthritis are protected from AD found that short‐term treatment of transgenic AD mice with the pro‐inflammatory cytokine granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) led to an increase in activated microglia, a 50% reduction in amyloid load, an increase in synaptic area, and improvement in spatial memory to normal. These results called into question the consensus view that inflammation is solely detrimental in AD. Here, we tested our hypothesis that modulation of the innate immune system might similarly be used to treat AD in humans by investigating the ability of GM‐CSF/sargramostim to safely ameliorate AD symptoms/pathology. Methods: A randomized, double‐blind, placebo‐controlled trial was conducted in mild‐to‐moderate AD participants (NCT01409915). Treatments (20 participants/group) occurred 5 days/week for 3 weeks plus two follow‐up (FU) visits (FU1 at 45 days and FU2 at 90 days) with neurological, neuropsychological, blood biomarker, and imaging assessments. Results: Sargramostim treatment expectedly changed innate immune system markers, with no drug‐related serious adverse events or amyloid‐related imaging abnormalities. At end of treatment (EOT), the Mini‐Mental State Examination score of the sargramostim group increased compared to baseline ( P = .0074) and compared to placebo ( P = .0370); the treatment effect persisted at FU1 ( P = .0272). Plasma markers of amyloid beta (Aβ40 [decreased in AD]) increased 10% ( P = .0105); plasma markers of neurodegeneration (total tau and UCH‐L1) decreased 24% ( P = .0174) and 42% ( P = .0019), respectively, after sargramostim treatment compared to placebo. Discussion: The innate immune system is a viable target for therapeutic intervention in AD. An extended treatment trial testing the long‐term safety and efficacy of GM‐CSF/sargramostim in AD is warranted.